The Effect of Solvent Type on Oil Yield on Essential Oil of Sweet Orange Peel Extract (Citrus X Sinensis) - Anwar Syahadat; Hasni Yaturramadhan; Ayus Diningsih (Journal of Public Health and Pharmacy)
Introduction: Citrus fruits can be processed into various types of preparations that are very useful. Sweet orange (Citrus X sinensis) is a type of orange that is consumed by squeezing it into a drink. So far, sweet orange peels (Citrus X sinensis) have not been fully utilized and become waste that is thrown away. Meanwhile, the peels of citrus fruits have useful content, so that the peels of citrus fruits can be processed into products that are useful for the community. Wet sweet orange peel is better to use than dried sweet orange peel. This is because the sweet orange peel contains essential oils which have not completely evaporated so that the oil can be taken directly.